Identification of Familial Hodgkin Lymphoma Predisposing Genes Using Whole Genome Sequencing - Srivastava, Aayushi; Giangiobbe, Sara; Kumar, Abhishek; Paramasivam, Nagarajan; Dymerska, Dagmara; Behnisch, Wolfgang; Witzens-Harig, Mathias; Lubinski, Jan; Hemminki, Kari; Försti, Asta; Bandapalli, Obul Reddy (Frontiers in Bioengineering and Biotechnology, 2020)
Hodgkin lymphoma (HL) is a lymphoproliferative malignancy of B-cell origin that accounts for 10% of all lymphomas. Despite evidence suggesting strong familial clustering of HL, there is no clear understanding of the contribution of genes predisposing to HL. In this study, whole genome sequencing (WGS) was performed on 7 affected and 9 unaffected family members from three HL-prone families and variants were prioritized using our Familial Cancer Variant Prioritization Pipeline (FCVPPv2). WGS identified a total of 98564, 170550 and 113654 variants which were reduced by pedigree-based filtering to 18158, 465 and 26465 in families I, II and III, respectively. In addition to variants affecting amino acid sequences, variants in promoters, enhancers, transcription factors binding sites and microRNA seed sequences were identified from upstream, downstream, 5’ and 3’ untranslated regions. A panel of 565 cancer predisposing and other cancer-related genes and of 2383 potential candidate HL genes were also screened in these families to aid further prioritization. Pathway analysis of segregating genes with Combined Annotation Dependent Depletion Tool (CADD) scores > 20 was performed using Ingenuity Pathway Analysis software which implicated several candidate genes in pathways involved in B-cell activation and proliferation and in the network of “Cancer, Hematological disease and Immunological Disease”. We used the FCVPPv2 for further in silico analysis and prioritized 45 coding and 79 non-coding variants from the three families. Further literature-based analysis allowed us to constrict this list to one rare germline variant each in families I and II and two in family III. Functional studies were conducted on the candidate from family I in a previous study, resulting in the identification and functional validation of a novel heterozygous missense variant in the tumor suppressor gene DICER1 as potential HL predisposition factor. We aim to identify the individual genes responsible for predisposition in the remaining two families and will functionally validate these in further studies.